The Archaeobiology of Bears and Bear Ceremonialism in Minnesota - Mather, David (2019)
University of Minnesota Ph.D. dissertation. December 2019. Major: Anthropology. Advisor: Guy Gibbon. 1 computer file (PDF); xviii, 441 pages. American black bears (Ursus americanus) and brown/grizzly bears (Ursus arctos) are sacred animals to traditional members of the Dakota, Ojibwe, and other American Indian nations. This dissertation creates historic contexts for consideration of bears in Minnesota’s archaeological record, to aid indigenous archaeology and heritage management, and to provide a historical perspective for management of the state’s current black bear population. Archaeological sites in Minnesota contain occasional representations of bears in rock art, earthworks and portable art, and rare zooarchaeological finds of bear bones or teeth. In three cases, excavations have encountered large numbers of skull fragments representing dozens to hundreds of bears. Collectively these archaeological sites, features and artifacts are varied expressions of bear ceremonialism, within and beyond the scope described in the 1926 American Anthropologist article by A. Irving Hallowell. Minnesota is one of a few areas in the continental United States where black bears survived the pressures of overhunting and habitat loss in the late nineteenth and early twentieth centuries. Grizzly bears were once present on the Great Plains, including parts of Minnesota, but the closest living population today is in Yellowstone National Park. Minnesota bear finds are summarized for the Laurentian Mixed Forest, Eastern Broadleaf Forest, Tallgrass Aspen Parklands, and Prairie Parklands ecological provinces, as defined by the Ecological Classification System utilized by the Minnesota Department of Natural Resources, within the context of each provinces zooarchaeological record. The density of archaeological bear finds is greatest along the boundary between the Laurentian Mixed Forest and Eastern Broadleaf Forest. More detailed analysis was conducted on teeth from archaeological assemblages from the Christensen Mound (21SH1/16), Crace (21ML3) and Bear (21ML68) sites, with comparative analysis on recent black bear skulls of known life history from Chippewa National Forest. These studies allowed assessment of the age and sex structure of the bears at each site, indicating that while the assemblages appear superficially similar, different types of ceremonies are represented at each.